Emotional Design Analysis in Online Multimedia Learning - Agustin, Atiya Arifiyana; Dewi, Dyah Santhi (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
Online  learning  utilizes  multimedia  as  a  learning  medium.  Emotional  factors  are  often  ignored  in  multimedia learning  research.  Several studies  have  stated  that  emotional  factors  have  a  small  effect  on learning  outcomes but have a large effect on student motivation and willingness to learn. Therefore, the emotional factor deserves further investigation of its influence on multimedia learning. Multimedia learning used in the research is in the form of powerpoint (PPT) and video. Emotional factors were measured using the PANAVA-KS method. The best multimedia learning  design  is  a  design  that  can  help find  a multimedia learning  design  that  can evoke  positive emotions so that it can be used as a good learning medium.